The Effect of Habituation of Dhuha on the Religiosity of Santri - Zulfia Rizki Anggraini; Saiful Anwar (EDUKASI : Jurnal Pendidikan Islam (e-Journal), 2021)
The background of this research is that the pesantren has responsibility for the education of its students, both general education and Islamic religious education. In this case, Arissalah Islamic Boarding School Ponorogo has several dormitory activities to support the level of religiosity of students, one of which is the habit of praying dhuha. The purpose of this study was to determine: 1) the habit of praying dhuha; 2) santri religiosity; and 3) the significant effect of habituation of dhuha prayer on students' religiosity. This research uses quantitative research. An analytical tool to test the truth of the method used is a questionnaire and documentation. The approach used is the type of correlation. Data collection was carried out at Arissalah Islamic Boardig School Ponorogo with 40 respondents in KMI girl class II, III, V, and VI students. The results showed that students of KMI girl class II, III, V, and VI at Arissalah Islamic Boardig School had a high implementation of the dhuha prayer. The results also show a positive and significant influence between the dhuha prayer and the religiosity of students. This can be seen from the constant value of 35.102 and the regression coefficient of 0.382 with the linear regression equation, Y = 35.102 + 0.382X. To find out the effect of dhuha prayer on students' religiosity using the coefficient of determination, it is known that the coefficient of determination is 29.4%. In comparison, 70.6% of the religiosity variable is influenced by other factors outside the research that have not been disclosed.